Identity projects and nation in the literature of southern Peru. The cases of Enrique Rosas Paravicino and Feliciano Padilla Chalco - Terán Morveli, Jorge (2023)
The fundamental axis of our research is the question of Andeanness in contemporary Andean narrative, and its relation to the projects of nationhood proposed therein. Since the 1980s, the representation of the Andean has been reformulated by expanding the represented world of the Andes to other forms of Andeanness that include indigenous, mestizo and creole sectors -mistis-, overcoming the indigenist paradigm. Above all, South Andean narrators have proposed, through fiction, modalities of Andeanness and proposals of nationhood. Our research, as exploratory, studies two (2) of these modalities based on the variables mentioned above. Therefore, we start from the following corpus: the book of short stories Al filo del rayo (1987), by Enrique Rosas Paravicino (Cusco, 1948), in which a dynamic Andean world is represented in which diverse socio-cultural sectors coexist with their particular identities and, from there, an inclusive, integrating project of nation is formulated; and the short story La estepa calcinada (1984), by Feliciano Padilla Chalco (Lima, 1944-Puno, 2022), in which, also based on the recognition of identity diversity, the strengthening of the indigenous identity is highlighted, but, at the same time, the impossibility of crystallizing a model of nation.